PATIENTS' SLEEP QUALITY AND AFFECTING FACTORS ON POST MASTECTOMY - Serap KURTAR; Nigar ÜNLÜSOY DİNÇER (Rojan GÜMÜŞ, 2022)
This descriptive and cross-sectional study was conducted to determine sleep quality and factors affecting sleep in patients who have been operated on mastectomy surgery. The sample of the study is comprised of those patients (n=110) who visited general surgery outpatient clinic in an education and research hospital in Ankara between January 1 and July 30, 2020, for the check after their mastectomy surgery, agreed to participate in the study and met research criteria. The Patient Information Form and the Pittsburg Sleep Quality Index (PSQI) were used as data collection tools. The numbers and percentages, t-test and Kruskal Vallis Chi-Square, and Fisher's Exact Spearman Correlation analysis were used to evaluate the data. Written permission from the ethics committee and the institution, and written consent from the patients were obtained to conduct the study. After the mastectomy surgery of patients who participated in the study, the average PSQI score of them was 10.19 ± 3.44 (2-18). After the mastectomy surgery of the patients, it was determined that 60,9% of the patients had a decrease in sleep quality, 89,1% had poor sleep quality, and 81,8% had a change in the postoperative sleeping position. There was no statistically significant difference between the findings related to the characteristics of the patients and the PSQI mean scores (p> 0.05). According to the results of the study, patients who have poor sleep quality and changes in their sleep habits after mastectomy surgery should be given the training to improve sleep quality before discharging from the hospital. In the field of nursing, it is recommended to conduct experimental studies to increase the sleep quality of patients.